Peintures et gravures rupestres des Amériques : empreintes culturelles et territoriales proceedings of the XVIII UISPP World Congress (4-9 June 2018, Paris, France) : volume 2 : Session XXV-3 - Faugère, Brigitte 1958-; Costa, Philippe (Archaeopress Archaeology, 2020)
How does the study of rock art make it possible to culturally characterise its authors? What does it tell us about the function of sites? How and under what circumstances does it make it possible to delimit a cultural territory? The six articles in this volume provide case studies from Mexico, El Salvador, Costa Rica, French Guiana and Chile
"Available both in print and Open Access"--Homepage. - Conference proceedings. - Also issued in print: 2020. - Includes bibliographical references
Keywords: Petroglyphs / Latin America / Congresses; Rock paintings / Latin America / Congresses; Indians of Central America / Antiquities / Congresses; Indians of South America / Antiquities / Congresses; Felsbild; Lateinamerika; Konferenzschrift